DO AUDIT COMMITTEE CHAIR CHARACTERISTICS MATTER FOR CORPORATE TAX AVOIDANCE? EVIDENCE FROM INDONESIA - Nicklaus Stanley; Luky Patricia Widianingsih (Journal of Tax Policy, Economics, and Accounting (TAXPEDIA), 2026)
Abstract Corporate tax avoidance remains a complex issue, making the role of corporate governance mechanisms in shaping firms’ tax strategies increasingly important. Although prior studies have examined the board of directors, CEO characteristics, and audit committee attributes, the influence of the audit committee chair remains underexplored. This study investigates the impact of audit committee chair characteristics on corporate tax avoidance in Indonesian consumer cyclical firms. The examined characteristics include military connections, political connections, family affiliations, financial affiliations, and the number of positions held by the audit committee chair. Using 141 firm-year observations from 77 firms during 2021–2023, this study employs multiple linear regression, with tax avoidance proxied by the cash effective tax rate (CETR). Since CETR is inversely related to tax avoidance, higher CETR indicates lower tax avoidance. The findings show that military-connected audit committee chairs are associated with lower tax avoidance, whereas financial affiliations are associated with higher tax avoidance. Political connections, family affiliations, and the number of positions held have no significant effect. The study contributes to governance-based tax avoidance literature and offers insights for tax monitoring policies.   Abstrak Penghindaran pajak perusahaan merupakan isu kompleks sehingga peran mekanisme tata kelola perusahaan dalam membentuk strategi pajak semakin penting untuk dikaji. Meskipun penelitian sebelumnya telah membahas dewan direksi, karakteristik CEO, dan komite audit, pengaruh ketua komite audit masih relatif kurang diperhatikan. Penelitian ini menginvestigasi pengaruh karakteristik ketua komite audit terhadap penghindaran pajak perusahaan pada perusahaan sektor consumer cyclical di Indonesia. Karakteristik yang diteliti meliputi koneksi militer, koneksi politik, afiliasi keluarga, afiliasi keuangan, serta jumlah jabatan yang dipegang oleh ketua komite audit. Dengan menggunakan 141 observasi perusahaan-tahun dari 77 perusahaan selama periode 2021–2023, penelitian ini menerapkan regresi linier berganda, dengan penghindaran pajak diproksikan melalui cash effective tax rate (CETR). Karena CETR berhubungan terbalik dengan penghindaran pajak, CETR yang lebih tinggi menunjukkan penghindaran pajak yang lebih rendah. Hasil penelitian menunjukkan bahwa ketua komite audit berkoneksi militer berasosiasi dengan penghindaran pajak yang lebih rendah, sedangkan afiliasi keuangan berasosiasi dengan penghindaran pajak yang lebih tinggi. Koneksi politik, afiliasi keluarga, dan jumlah jabatan tidak berpengaruh signifikan.